Hesperidin alleviates zinc-induced nephrotoxicity via the gut-kidney axis in swine - Yang, Qingwen; Qian, Lv; He, Shanshan; Zhang, Chuanshi (Frontiers in Cellular and Infection Microbiology, 2024)
Zinc (Zn) is an essential trace element in animals, but excessive intake can lead to renal toxicity damage. Thus, the exploration of effective natural antagonists to reduce the toxicity caused by Zn has become a major scientific problem. Here, we found that hesperidin could effectively alleviate the renal toxicity induced by Zn in pigs. The results showed that hesperidin could effectively attenuate the pathological injury in kidney, and reduce autophagy and apoptosis induced by Zn, which evidenced by the downregulation of LC3, ATG5, Bak1, Bax, Caspase-3 and upregulation of p62 and Bcl2.Additionally, hesperidin could reverse colon injury and the decrease of ZO-1 protein expression. Interestingly, hesperidin restored the intestinal flora structure disturbed by Zn, and significantly reduced the abundance of Tenericutes (phylum level) and Christensenella (genus level). Thus, altered intestinal flora and intestinal barrier function constitute the gut-kidney axis, which is involved in hesperidin alleviating Zninduced nephrotoxicity. Our study provides theoretical basis and practical significance of hesperidin for the prevention and treatment of Zn-induced nephrotoxicity through gut-kidney axis.